Library of digital models and constructive simulations of structural elements. - Sánchez-Berrocal, Juan; Troyano-Moreno, Miguel (My University, 2023)
The aim of this communication is to describe the use of new technologies to obtain a library of digital models of structural elements and construction simulations to improve learning processes in the sujects of concrete structures and foundations. To this end, the Autodesk BIM tools Revit and Navisworks are used to obtain the 3D geometric model of the structural elements, which includes both the shapes and the reinforcement and formwork, the Autodesk 3DS Max tool to create the animations that represent the construction simulations, the Sketchfab web platform to visualise the digital models and the YouTube platform to visualise the costruction simulations. These web platforms allow not only to visualise the elements of the library but also to embed these components in other web platforms, such as the Moodle learning platform, and in the UMA CV.
Keywords: Construcción - Simulación por ordenador; Diseño arquitectónico - Estudio y enseñanza; Ingeniería de estructuras; BIM; Digital model; Reinforced concrete; Construction simulation; Teaching reinforced concrete